Process Management Tools for Operation Efficiency in Logistics: Case Study - Snarskė, Olga (Vilnius University Proceedings, 2025)
In the context of increasing complexity in global supply chains, effective process management has become a crucial determinant of operational efficiency in large-scale logistics companies. This study aims to assess the impact of an advanced process management system, introduced in 2022 within one of the largest logistics enterprises, with the objective of optimising internal communication and streamlining operations. Utilising a rigorous analytical framework, the research demonstrates significant improvements in information flow, transparency, and organisational clarity. The system has shown notable efficacy in key areas, including the implementation of quality and environmental policies, the optimisation of core operational processes, and the enhancement of management documentation. The findings suggest that process management contributes substantially to the achievement of higher operational efficiency and process optimisation. Furthermore, this study offers practical recommendations that may guide similar organisations in improving their logistical performance through systematic process management innovations.
Keywords: process management; operational efficiency; process management system (PMS)